2023
DOI: 10.5888/pcd20.220400
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Geographic Patterns of Self-Reported Short Sleep Duration Among US Adults, 2020

Abstract: We estimated the prevalence of short sleep duration (<7 hours per day) among US adults aged 18 years or older by using 2020 Behavioral Risk Factor Surveillance System data. Nationally, 33.2% of adults reported short sleep duration. We identified disparities across sociodemographic characteristics, including age, sex, race and ethnicity, marital status, education, income, and urbanicity. Counties with the highest model-based estimates of short sleep duration clustered in the Southeast and along the Appalachian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…This cohort study assessing daily sleep duration, dietary habits, and the risk of T2D among individuals in the UK Biobank cohort 38 to 71 years of age found that habitual short sleep duration was associated with increased risk of developing T2D and that this association persisted even among participants who maintained a healthy diet. Many adults struggle to sleep 7 to 8 hours per day . As suggested by laboratory studies, a lack of sleep may contribute to the development of T2D through various mechanisms, such as impaired cellular insulin sensitivity, a skeletal muscle energy metabolism shifted toward nonglucose oxidation, increased activity of the sympathetic nervous system, and altered gut microbiota composition .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This cohort study assessing daily sleep duration, dietary habits, and the risk of T2D among individuals in the UK Biobank cohort 38 to 71 years of age found that habitual short sleep duration was associated with increased risk of developing T2D and that this association persisted even among participants who maintained a healthy diet. Many adults struggle to sleep 7 to 8 hours per day . As suggested by laboratory studies, a lack of sleep may contribute to the development of T2D through various mechanisms, such as impaired cellular insulin sensitivity, a skeletal muscle energy metabolism shifted toward nonglucose oxidation, increased activity of the sympathetic nervous system, and altered gut microbiota composition .…”
Section: Discussionmentioning
confidence: 99%
“…Many adults struggle to sleep 7 to 8 hours per day. 1 As suggested by laboratory studies, a lack of sleep may contribute to the development of T2D through various mechanisms, such as impaired cellular insulin sensitivity, 6 a skeletal muscle energy metabolism shifted toward nonglucose oxidation, 25 increased activity of the sympathetic nervous system, 26 and altered gut microbiota composition. 4 , 27 Consequently, the high prevalence of individuals with short sleep duration may contribute to the projected global escalation of T2D prevalence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another sleep disorder is sleep duration. One third of the American adults reported shorter sleep duration than the amount recommended by the National Sleep Foundation [22]. Nonoptimal sleep durations have been correlated with adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%